Cytotoxicity and genotoxicity assays of halobenzoquinones disinfection byproducts using different human cell lines. (10th April 2020) - Li, Jiabao; Zhang, Haifeng; Han, Yingnan; Chao, Huang; Ma, Mei; Yang, Min
Abstract: Recently, halobenzoquinones (HBQs) disinfection byproducts, including 2, 6‐dichloro‐1, 4‐benzoquinone (DCBQ), 2, 6‐dichloro‐3‐methyl‐1, 4‐benzoquinone (DCMBQ), 2, 3, 6‐trichloro‐1, 4‐benzoquinone (TCBQ), and 2, 6‐dibromobenzoquinone (DBBQ), have been of increasing concern due to their reported ability to induce oxidative damage, and thus genotoxicity. However, data on the risk of genotoxicity due to chromosomal damage by HBQs are still scarce. Here, the cytotoxicity and genotoxicity of the four HBQs were assessed using human cell lines (bladder cancer 5637 cells, colon carcinoma Caco‐2 cells, and gastric MGC‐803 cells). The four HBQs exhibited significant concentration‐response relationships in all the three cell lines. Cytotoxicity of DCBQ, DCMBQ, TCBQ, and DBBQ, represented by the 50% concentration of inhibition (IC50 ) values, were 80.8–99.5, 41.0–57.6, 122.1–146.6, and 86.9–93.8 μM, respectively. The lowest effective concentrations for cellular micronuclei induction in the cell lines by DCBQ, DCMBQ, TCBQ, and DBBQ were 50–75, 20–41.5, 87.4–100, and 50 μM, respectively. 5637 and Caco‐2 cells were more sensitive to the cytotoxic and genotoxic effects of HBQs than MGC‐803 cells. These results show that HBQs can induce chromosomal damage; DCMBQ induced the highest cytotoxicity and genotoxicity in all the cell lines, and TCBQ caused the least toxicity.